ABSTRACT TRANSPORT GOVERNANCE A Case Study of Container Transport Services in Gedebage Dry port - ZAKY (NIM : 24008038) ; Pembimbing : Ir. Indra B. Syamwil, MSc. Ph.D, A.
Dry port development as a container terminal is one of the facilities provided by the Government in the transport sector designated as the development of the sea ports due to their maximum capacity and distant location from the industrial areas serving as an exit and incoming good route, checking of goods by customs, as well provide temporary storage. The decrease in performance of Gedebage Dryport in recent years has resulted in failure to achieve its founding purpose. The government’s efforts to make Gedebage dry port’s performance effective will be meaningless if the understanding of the changes occurring on the industrial needs of transportation services have not been accomplished. To see the causes of degradation of Gedebage Dryport performance, the definition of the problems in managing this dryport from various viewpoints of the parties need to be viewed and analyzed, because it will affect the strategy to be taken. There are three things that would be seen from this study, first, how far the needs of industry in Bandung and the surrounding areas toward container cargo transport service through Gedebage Dryport, secondly, the availability of cargo container transportation services through Gedebage Dryport; third, how the services in Gedebage Dryport held in transport governance perspective. Therefore, descriptive qualitative method with case study approach is adopted to learn and understand intensively about the governance of transportation to achieve the expected goals. The study shows that: (i) transport mode needed by industry in the hinterland regions of Gedebage dryport has been in line with the development of Bandung area as the city of factory outlet; the construction of toll road from Jakarta to Bandung and declining productivity of the textile / garment due to the lack of ground water , raw materials, and the existence of competition and the global crisis. (II) The insufficient infrastructure facilities in Gedebage dry port in regard with transportation networks, facilities, and service procedures that are still an obstacle that needs improvement. (iii) the lack of interaction between stakeholders and relevant agencies causing the aspects considered in the decision making to improve container transport system through Gedebage dryport face problems. So, it is important to interact and have shared commitment to the achievement of Gedebage dryport of development goals in manifesting a good transportation system in accordance with the expected goals.